Penggunaan Medial Arch Support pada Kemampuan Motorik Kasar Siswa kepada Siswa, Guru, dan Orang Tua - Muhammad Syafii; Atika Febri Anggriani (Poltekkes Kemenkes Surakarta, 2020)
Background: Gross motor skills are the ability to move limbs that involve nerves, bones, and muscles, to perform certain activities (balance standing, walking, running, and jumping). To be able to do this, a person needs a normal body structure including the foot. A person will experience obstacles when the foot has a structural abnormality, one of which is the flat foot. Flat foot is a condition where the foot does not have a normal arch / flat foot. One of the treatments performed on flat foot sufferers is by giving foot orthosis in the form of Medial Arch Support. Medial arch support is a tool used to improve stability and improve walking function. Methods: According to a preliminary study conducted at SDN 1 Tohudan there were 47 students from grades 3 to 6 who experienced flat foot. This is known from the results of early detection of flat foot carried out at SDN 1 Tohudan. The approach method to be chosen is (1) Assessment for early detection of flat foot conditions, (2) health promotion by training for students, parents, and teachers to increase knowledge about flat foot problems that have an impact on children's gross motor skills so it needs to be done. intervention with the use of medial arch support, with the aim of improving students' gross motor skills. Results: After community service activities run, the understanding of students, parents, and teachers who are the targets / targets in this activity gets better, they become better at understanding the basics of flat foot, which results in a decrease in gross motor skills and increasingly realizes the importance of handling it by using medial arch support. Conclusions: The implementation of community service activities can increase the knowledge of students, teachers and parents about the effect of using medial arch support on the gross motor skills of students with flat foot.